Penyelesaian Sengketa Perbankan Syariah di Pengadilan Agama - Ramlah Ramlah (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2012)
In the era of reformation Religious Courts authority increases in economic shari'a as stipulated in Article 49 Amendment UU No. 3 of 2006 on Islamic Courts. In this case if the dispute Shariah banking occurs due to a dispute aqad (agreement) between the parties which resolve is the governing body of Arbitration, while the decision of peace carried out by the Islamic court.